Low beta repetitive transcranial magnetic stimulation to human dorsolateral prefrontal cortex during object recognition memory sample presentation, at a task related frequency observed in local field potentials in homologous macaque cortex, impairs subsequent recollection but not familiarity - Wu, Z; Kavanova, M; Hickman, L; Boschin, E; Galeazzi, JM; Verhagen, L; Ainsworth, M; Pedreira, C; Buckley, MJ (Wiley, 2021)
According to dual-process signal detection (DPSD) theories, short and long-term recognition memory draw upon both familiarity and recollection. It remains unclear how primate prefrontal cortex (PFC) contributes to these processes but frequency-specific neuronal activities are considered to play a key role. In Experiment 1, non-human primate (NHP) local field potential (LFP) electrophysiological recordings in macaque left dorsolateral PFC (dlPFC) revealed performance-related differences in a low beta frequency range during the sample presentation phase of a visual object recognition memory task. Experiment 2 employed a similar task in humans and targeted left dlPFC (and vertex as a control) with repetitive transcranial magnetic stimulation (rTMS) at 12.5Hz during occasional sample presentations. This low beta-frequency rTMS to dlPFC decreased DPSD derived indices of recollection, but not familiarity, in subsequent memory tests of the targeted samples after short delays. The same number of rTMS pulses over the same total duration albeit at a random frequency had no effect on either recollection or familiarity. Neither stimulation protocol had any causal effect upon behaviour when targeted to the control site (vertex). In this study our hypotheses for our human TMS study were derived from our observations in NHPs; this approach might inspire further translational research through investigation of homologous brain regions and tasks across species using similar neuroscientific methodologies to advance the neural mechanism of recognition memory in primates.